FINANCIAL AND SOCIAL BARRIERS IN CONDUCTING RESEARCH AT POSTGRADUATE LEVEL IN PUBLIC AND PRIVATE SECTOR UNIVERSITIES OF KHYBER PAKHTUNKHWA - Iqbal, Akhtar; Shah, Manzoor Hussain; Bashir, Zahid; Iqbal, Javed; Khan, Muhammad Muddassar (International Journal of Psychosocial Rehabilitation, 2020)
Research highly contributes in the overall development of a country. To achieve this reality, Higher Education Commission (HEC) of Pakistan plays a significant role in establishing a sound base of research culture in the country. Despite the fact, researchers are facing number of issues during research which need to be addressed. Objectives of the study were to find out and compare the opinions of the respondents concerning different barriers in the execution of research in government and private level Universities of Khyber Pakhtunkhwa, Pakistan. As a study sample, the scholar selected eight (08) universities four from public and four from private level at random. It comprised of 640 respondents having four each from social and natural sciences. The researcher collected five twenty one responses. For getting feedback from the respondents, a questionnaire containing fifteen items was designed. One open-ended question was developed to get more responses. Data was evaluated applying statistical tools including percentage, mean, t–test and standard deviation. The open-ended questions were evaluated applying the method of content analysis. Results of the research study showed that there was uniformity among the views of the majority of the respondents with minor differences about financial and social barriers which are creating hurdles in carrying out research. After identifying and comparing the opinions of the respondents, areas are suggested where future efforts may be built on the findings of the research study.